2005
DOI: 10.1016/j.jvs.2005.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the treatment with prostaglandin E-1 in venous ulcers of the lower limbs

Abstract: This study demonstrates the effectiveness of PGE-1 in reducing the healing time of venous ulcers, suggesting that venous ulcers should also be considered ischemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…An intravenous treatment with prostaglandin E 1 was tested in VLUs and demonstrated reduced time to healing, improved complete healing rate, and improvement in other outcomes pertinent to chronic venous disorders, such as edema and venous symptoms. [464][465][466] The constraint of intravenous infusion (3 hours daily for 6 weeks), however, makes this therapy difficult to recommend. The discovery of the involvement of leukocytes in the pathophysiologic mechanism of VLUs has opened another pathway for successful investigations.…”
Section: [Best Practice]mentioning
confidence: 99%
“…An intravenous treatment with prostaglandin E 1 was tested in VLUs and demonstrated reduced time to healing, improved complete healing rate, and improvement in other outcomes pertinent to chronic venous disorders, such as edema and venous symptoms. [464][465][466] The constraint of intravenous infusion (3 hours daily for 6 weeks), however, makes this therapy difficult to recommend. The discovery of the involvement of leukocytes in the pathophysiologic mechanism of VLUs has opened another pathway for successful investigations.…”
Section: [Best Practice]mentioning
confidence: 99%
“…In a randomized trial, infusion of prostaglandin E1 vs. placebo for 20 days demonstrated that all the venous ulcers were healed at 4 months, and a significant decrease in ulcer area were observed at 80 days. It was concluded that prostaglandin E1 may be beneficial in venous ulcer healing, possibly by improving the alterations in the microcirculation and hypoxemia associated with venous ulcer formation [103].…”
Section: Management Of Varicose Veinsmentioning
confidence: 99%
“…Prostaglandins that inhibit platelet aggregation, leukocyte activation and capillary permeability and promote venodilation and fibrinolysis can be useful. In a randomized trial, infusion of prostaglandin E1 vs. placebo for 20 days showed healed venous ulcers at 4 months, and a decrease in ulcer area at 80 days, suggesting beneficial effects in venous ulcer healing, possibly by improving the microcirculation and reducing the hypoxemia associated with venous ulcer [320]. …”
Section: Introductionmentioning
confidence: 99%